2004
DOI: 10.1177/026119290403201s55
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the US High Production Volume (HPV) Chemical-testing Programme: A Study in (Ir)Relevance, Redundancy and Retro Thinking

Abstract: Under the US Environmental Protection Agency (EPA) High Production Volume (HPV) Challenge Programme, chemical companies have volunteered to conduct screening-level toxicity tests on approximately 2800 widely-used industrial chemicals. Participating companies are committed to providing available toxicity information to the EPA and presenting testing proposals for review by the EPA and posting on the EPA Web site as public information. People for the Ethical Treatment of Animals (PETA) and a coalition of animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…To summarize, all are agreed that there is a need to reduce rather than eliminate animal experimentation. At the same time, efforts must continue to find suitable replacements for animal experimentation as well as more refined techniques that avoid the use of intact live animals [ 37 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Ethical Issues In Animal Experimentationmentioning
confidence: 99%
“…To summarize, all are agreed that there is a need to reduce rather than eliminate animal experimentation. At the same time, efforts must continue to find suitable replacements for animal experimentation as well as more refined techniques that avoid the use of intact live animals [ 37 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Ethical Issues In Animal Experimentationmentioning
confidence: 99%
“…An early review of the HPV program by the Physicians Committee for Responsible Medicine (Cardello 2001) documented serious flaws in test plans submitted by sponsors, including a ) failure to report existing hazard information and to group structurally or toxicologically similar chemicals; b ) proposed animal tests that were beyond the scope of the HPV program; and c ) lack of enforcement by the U.S. EPA of agreed-upon animal welfare principles. A subsequent evaluation of the HPV program by Nicholson et al (2004) showed that many of the same problems reported by Cardello (2001) still existed. In addition, they found that testing was proposed for chemicals with known toxicities and for irrelevant end points when the primary hazard was high and well known, and that testing in vivo was proposed when valid in vitro methods were available.…”
Section: Discussionmentioning
confidence: 68%
“…However, some sponsors still proposed animal tests, even when a chemical’s properties rendered the results of these tests meaningless. In the API’s initial test plan for the Petroleum Gases Category, its Petroleum HPV Testing Group (PHTG) proposed separate acute mammalian, repeated dose, reproductive, and developmental toxicity tests on each of the individual gases ethane, butane, propane, and isobutane, even though these gases are explosive at concentrations below those at which health effects are observed and have been shown to act primarily as simple asphyxiants (Nicholson et al 2004). After receiving comments from APOs and the U.S. EPA, the PHTG reconsidered its testing proposal and eliminated from its revised test plan all acute mammalian tests and all separate reproductive and developmental toxicity tests on individual gases (Twerdok 2001).…”
Section: Discussionmentioning
confidence: 99%
“…(Nikfar et al, 2014) chemicals can be considered pseudo-persistent chemicals because of their continuous emission to the environment, even if their half-lives are short (Bergman et al, 2012;Daughton, 2003). These chemicals plus POPs can be a great source of concern if vulnerable subpopulations are exposed to amounts that result in adverse effects (Nicholson et al, 2004). The National Health and Nutrition Examination Survey, a wellknown targeted biomonitoring study, includes a few hundred preselected chemicals for the survey.…”
Section: Systematic Analysis Of Human Exposure To Environmental Chemicalsmentioning
confidence: 99%